Ammonia Synthesis at Room Temperature and Atmospheric Pressure from N2: A Boron‐Radical Approach. (13th December 2022) - Bennaamane, Soukaina; Rialland, Barbara; Khrouz, Lhoussain; Fustier‐Boutignon, Marie; Bucher, Christophe; Clot, Eric; Mézailles, Nicolas
Abstract: Ammonia, NH3, is an essential molecule, being part of fertilizers. It is currently synthesized via the Haber–Bosch process, from the very stable dinitrogen molecule, N2 and dihydrogen, H2 . This process requires high temperatures and pressures, thereby generating ca 1.6 % of the global CO2 emissions. Alternative strategies are needed to realize the functionalization of N2 to NH3 under mild conditions. Here, we show that boron‐centered radicals provide a means of activating N2 at room temperature and atmospheric pressure whilst allowing a radical process to occur, leading to the production of borylamines. Subsequent hydrolysis released NH4 +, the acidic form of NH3 . EPR spectroscopy supported the intermediacy of radicals in the process, corroborated by DFT calculations, which rationalized the mechanism of the N2 functionalization by R2 B radicals. Abstract : Boron‐centered radicals, generated by reduction of R2 BCl derivatives, react with N2 all the way to borylamine formation. DFT calculations rationalize the reduction/functionalization process, involving N−N bond splitting. Hydrolysis of the mixture yields NH4 + . Radical addition to N2 provides a new strategy for N2 fixation.